SCATTERING OF CIRCULAR CAVITY IN CIRCULAR DOMAIN TO SH WAVES - WANG Ping; JIANG ShanTao (Jixie qiangdu)
The scattering problem of the circular cavity in the circular domain to the elastic waves is one of the main research objects in NDT（ Non-destructive testing） applications which has not been solved theoretically till now,the complex method,special function addition formulae and the wave function expansion method are employed to study the dynamic response problem of the circular cavity defect in the circular domain to the out-of-plane distributing loading acting on the outside of the circular domain,theoretical computation method of the stress concentration factors（ DSCF） on the boundary of the circular cavity defect is given,and the variations of the DSCF of the defect boundary along with the disturbing frequency and the loading location are investigated,numerical examples are given to verify the theoretical conclusions and show the influence of the boundaries and the loads to DSCF.